1997
DOI: 10.1037/0096-1523.23.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention in a reaching task: Effect of normal aging and alzheimer's disease.

Abstract: This study examined the ability of young adults, older adults, and older adults suffering from Alzheimer's disease (AD) to perform a selective reaching task. Normal aging did not increase interference caused by distractors. In contrast, patients with AD showed massively increased effects of distractor interference. AD patients showed a high probability of making responses to distractor items. The proportion of these incorrect responses was related to the inability to use inhibitory processes, which increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 29 publications
6
36
1
Order By: Relevance
“…Tipper, Lortie, and Baylis (1992; Experiment 1), for example, have already documented the interference effects on target ϩ distractor trials compared with target-alone trials in normal subjects as have Meegan and Tipper (1998) (see also data from patients with Alzheimer's disease on a similar paradigm; Simone & Baylis, 1997). Similar results, albeit from a more complex experiment and measurement procedure, have also been obtained in subsequent studies Tipper, Howard, & Jackson, 1997).…”
Section: Neglect and The Processing Of Contralateral Informationsupporting
confidence: 58%
See 1 more Smart Citation
“…Tipper, Lortie, and Baylis (1992; Experiment 1), for example, have already documented the interference effects on target ϩ distractor trials compared with target-alone trials in normal subjects as have Meegan and Tipper (1998) (see also data from patients with Alzheimer's disease on a similar paradigm; Simone & Baylis, 1997). Similar results, albeit from a more complex experiment and measurement procedure, have also been obtained in subsequent studies Tipper, Howard, & Jackson, 1997).…”
Section: Neglect and The Processing Of Contralateral Informationsupporting
confidence: 58%
“…First, we need to document the presence and extent of interference from distractors in normal subjects in the particular experimental paradigm we utilize. Second, some, although not all, studies have shown that older subjects are more susceptible to interference than are their younger counterparts, especially in more demanding tasks and because the patients who participate in this study are older, age-matched control subjects are important (Nebes & Madden, 1983;Simone & Baylis, 1997;Tipper, 1991). All subjects were right-handed, had normal or corrected-to-normal visual acuity, and consented to participate.…”
Section: Subjectsmentioning
confidence: 96%
“…This finding is consistent with recent reports of individual differences in the negative priming effect. These studies have shown that certain groups-in particular, Alzheimer's patients, schizophrenics, children, and older adultsoften show reduced negative priming (Cohen & ServanSchreiber, 1992;Dempster, 1992;Hasher & Zacks, 1988;Simone & Baylis, 1997). Most applicable to the results presented here is a recent study by Conway, Tuholski, Shisler, and Engle (1999).…”
Section: Discussionmentioning
confidence: 73%
“…In Experiment 1, we examined the pattern of distractor interference in a selective reaching task involving a much smaller targetdistractor separation than that typically used by Tipper and colleagues (Meegan & Tipper, 1998Simone & Baylis, 1997;Tipper et al, 1992). In addition, the effect of eye position on distractor interference was assessed.…”
Section: Experiments 1: Small Target-distractor Separationmentioning
confidence: 99%